Business models in crypto - Stolár, František; Jedlinský, Jakub; Abdallah, Kareem Issam; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
This bachelor's thesis explores the potential of cryptocurrencies and blockchain technology with various business models. The research focuses on identifying existing business models in crypto in the Czech Republic and proposing innovative blockchain-based solutions in supply chain management. Through thematic analysis and grounded theory methodologies, the study highlights key challenges, including regulatory uncertainties, security concerns, and knowledge gaps, compared by opportunities for innovation decentralization and sustainability. A comprehensive as-is analysis highlights current business models in crypto whilst being supported by a SWOT analysis framework to identify strengths, weaknesses, opportunities, and threats in the Czech crypto sector. The proposed business model utilizes blockchain’s characteristic properties – transparency, traceability, and automation – to address inefficiencies in supply chains. This thesis offers a practical plan for implementation as well as a practical application demonstrated using the supply chain network of Daimler Truck Customer Service & Parts s.r.o. focusing on enhanced operation efficiency, real-time data access, and origin traceability from the source to the end customer. The findings emphasize the importance of tailored solutions, education, and regulatory alignment for successful adoption. This thesis contributes to the growing discourse on integrating blockchain-based solutions into traditional industries to make way for more sustainable and efficient business practices.
Vedoucí práce: Jakub Jedlinský
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses